2020
DOI: 10.1002/osp4.396
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of IL‐6 gene expression in human adipose tissue after sleeve gastrectomy surgery

Abstract: Objective: There is increasing evidence that immune cell interactions in adipose tissue contribute to the development of metabolic dysfunction. Pro-inflammatory cytokines have been shown to mediate insulin resistance, and the presence of macrophages is a salient feature in the development of obesity. The present study aimed to evaluate adipocyte size and macrophage activation in women before and 3 months after laparoscopic vertical sleeve gastrectomy (VSG). Methods: Subcutaneous abdominal adipose tissue biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Studies have reported that pro-inflammatory cytokines like interleukin 6 and interleukin 18 are elevated in obesity and that this occurs in parallel with changes to other inflammatory mediators as well as the development of insulin resistance ( 40-42 ). We found that adipose tissue expression of genes IL6 and IL18 was reduced post-RYGB, which is in agreement with some previous studies showing reduced plasma levels following weight loss ( 41 , 43 ). This was seen from 24 weeks, and thus anti-inflammatory effects in adipose tissue may occur later than, and potentially as a consequence of, reduced systemic inflammation since CRP and WBC had been markedly reduced already at 4 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that pro-inflammatory cytokines like interleukin 6 and interleukin 18 are elevated in obesity and that this occurs in parallel with changes to other inflammatory mediators as well as the development of insulin resistance ( 40-42 ). We found that adipose tissue expression of genes IL6 and IL18 was reduced post-RYGB, which is in agreement with some previous studies showing reduced plasma levels following weight loss ( 41 , 43 ). This was seen from 24 weeks, and thus anti-inflammatory effects in adipose tissue may occur later than, and potentially as a consequence of, reduced systemic inflammation since CRP and WBC had been markedly reduced already at 4 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…This is certainly related to the different course, nature, duration, and effectiveness of interventions, as well as the differences in the number and type of health problems in the studied patients. Interventions that result in high percentages of weight loss in a relatively short period of time—in the case of interventions involving a very-low-calorie diet (VLCD) [ 56 ] or bariatric surgery [ 58 , 59 , 60 ]—clearly confirm the effect of weight loss on the reduction in the IL-6 and/or TNF-α expression in AT. However, in bariatric patients, this only applies to those with a high initial BMI, most often associated with class III obesity (BMI ≥ 40) [ 50 , 51 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…While obesity leads to increased IL-6 production in WAT, weight reduction induced by caloric restriction or laparoscopic vertical sleeve gastrectomy was paralleled by reduced mRNA and protein levels of IL-6 in subcutaneous WAT of human subjects (3,9). Moreover, IL-6 signaling in WAT may be critically involved in the regulation of weight loss induced by physical activity.…”
Section: Expression Of Il-6 In White Adipose Tissuementioning
confidence: 99%